penyusunan dan perancang ulang laporan keuangan dan perpajakan pada umkm soto bunda hariyanti berdasarkan sak emkm dengan menggunakan microsoft excel - Rusmawati Rusman (LP2M Politeknik Jambi, 2026)
Abstract Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, yet most MSMEs still face challenges in preparing financial reports and complying with tax obligations. The Soto Bunda Hariyanti MSME is one such business that does not yet have a structured financial recording system in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The research method used was a qualitative descriptive method with a case study approach. Data were obtained through interviews, observations, and documentation of the business's financial transactions. The research stages included identifying the current recording system, designing a financial report format in accordance with SAK EMKM, preparing transaction journals, general ledgers, profit and loss reports, statements of financial position, and relevant tax calculations using Microsoft Excel. The results showed that implementing a Microsoft Excel-based recording system resulted in more systematic, accurate, and compliant financial reports in accordance with SAK EMKM. Furthermore, the tax restructuring process helped business owners understand their tax obligations more accurately and in a planned manner. Keywords: SAK EMKM, financial reports, taxation, MSMEs, Microsoft Excel